Pengembangan Video Gerak dan Lagu Anti Bullying Untuk Siswa Sekolah Dasar - Nadia Kurnia Sari; Andika Gutama; Cicilia Ika Rahayu Nita (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Bullying in schools is currently a serious concern for the education and health services because bullying cases are increasingly widespread, especially in the school environment. Without bullying incidents, learning activities at school become enjoyable, so alternative solutions are needed to minimize bullying cases that occur in elementary schools. This research aims to describe the process, feasibility and practicality of developing anti-bullying movement videos and songs. This research uses a development research method with a 4D model consisting of Define, Design, Develop, Dessiminat. The data used in this research are qualitative data and quantitative data. The results of the feasibility test for the Anti-Bullying Movement Video and Song met the "Very Eligible" criteria with percentage results of 93% material experts, 96% language experts and 97.5% media experts. The practicality test received the "Very Practical" category with a percentage result of 96% by teachers, and 93% in the students' practicality test. Thus, anti-bullying motion video and song products are suitable for use in elementary schools and are practical and can be used to reduce bullying incidents in elementary schools. At the testing stage, the effectiveness of anti-bullying movement videos and songs was declared to be very effective.